Multi-objective constructive cooperative coevolutionary optimization of robotic press-line tending. Issue 10 (3rd October 2017) - Glorieux, E.; Svensson, B.; Danielsson, F.; Lennartson, B.
ABSTRACT: This article investigates multi-objective optimization of the robot trajectories and position-based operation-coordination of complex multi-robot systems, such as press lines, to improve the production rate and obtaining smooth motions to avoid excessive wear of the robots' components. Different functions for handling the multiple objectives are evaluated on real-world press lines, including both scalarizing single-objective functions and Pareto-based multi-objective functions. Additionally, the Multi-Objective Constructive Cooperative Coevolutionary ( ) algorithm is proposed, for Pareto-based optimization, which uses a novel constructive initialization of the subpopulations in a co-adaptive fashion. It was found that Pareto-based optimization performs better than the scalarizing single-objective functions. Furthermore, gives substantially better results compared to manual online tuning, as currently used in the industry. Optimizing robot trajectories and operation-coordination of complex multi-robot systems using the proposed method with significantly improves productivity and reduces maintenance. This article hereby addresses the lack of systematic methods for effectively improving the productivity of press lines.